Conscious Sedation with Nitrous Oxide - A Technique with a Potential as Wide as General Anesthesia Itself. - Naithani, Manish; Gami, Neha; Puri, Arun (Asian Journal of Medical Sciences, 2013)
Though conscious sedation is an established technique for alleviating pain and anxiety in dentistry; it has been underutilized by other medical and surgical specialties. Satisfied fully with its traditional use, and completely convinced that it has a role as wide, and as important, as general anesthesia itself, we venture to recommend its utilization for a variety of procedures. Asian Journal of Medical Science, Volume-4 (2013), Pages 3-4 DOI: http://dx.doi.org/10.3126/ajms.v4i4.8303